2000
DOI: 10.1074/jbc.m001386200
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Linkage between the S1 Site, the Na+Site, and the Ca2+ Site in the Protease Domain of Human Coagulation Factor Xa

Abstract: The serine protease domain of factor Xa (FXa) contains a sodium as well as a calcium-binding site. Here, we investigated the functional significance of these two cation-binding sites and their thermodynamic links to the S1 site. Kinetic data reveal that Na ؉ binds to the substrate bound FXa with K d ϳ39 mM in the absence and ϳ9.5 mM in the presence of Ca 2؉ . Sodium-bound FXa (sodium-Xa) has ϳ18-fold increased catalytic efficiency (ϳ4.5-fold decrease in K m and ϳ4-fold increase in k cat ) in hydrolyzing S-2222… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
69
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 40 publications
10
69
0
Order By: Relevance
“…These results suggest that similar to thrombin, the conformations of the 186-loop and the 225-loop are allosterically coupled, and thus the dramatic impairment in the amidolytic activity of the K186A mutant may also be caused by its inability to effectively interact with Na ϩ . These results are also in an agreement with previous thermodynamic linkage analysis that demonstrated that the binding of Na ϩ to the 225-loop of fXa allosterically modulates the specificity of the S1 site (Asp 189 ) interaction with the P1-Arg of substrates (16,17). To determine whether the mutagenesis of the 186-loop influences the S1 site specificity of the mutants, their ability to bind to the S1 site specific probe of the trypsin-like serine proteases PAB was examined.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…These results suggest that similar to thrombin, the conformations of the 186-loop and the 225-loop are allosterically coupled, and thus the dramatic impairment in the amidolytic activity of the K186A mutant may also be caused by its inability to effectively interact with Na ϩ . These results are also in an agreement with previous thermodynamic linkage analysis that demonstrated that the binding of Na ϩ to the 225-loop of fXa allosterically modulates the specificity of the S1 site (Asp 189 ) interaction with the P1-Arg of substrates (16,17). To determine whether the mutagenesis of the 186-loop influences the S1 site specificity of the mutants, their ability to bind to the S1 site specific probe of the trypsin-like serine proteases PAB was examined.…”
Section: Resultssupporting
confidence: 75%
“…For instance, the binding of both Ca 2ϩ to the 70-loop and Na ϩ to the 225-loop is known to markedly promote the activity of fXa toward synthetic substrates and natural target inhibitors (14,15). Recent thermodynamic linkage analyses have indicated that both of these metal ion binding sites are energetically linked in fXa (15)(16)(17). Moreover, the same studies have demonstrated that the Na ϩ and the S1 sites of fXa are also allosterically linked (16,17).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Na þ binds at a different site below the primary specificity pocket (S1) of the enzyme and is coordinated by residues neither directly involved in catalysis nor substrate recognition. In the presence of Na þ , activity of coagulation factors VIIa (10), IXa (11) and Xa (12) and activated protein C (13) is enhanced 3-to 10-fold. The effect of Na þ on thrombin is more pronounced (30-fold increase in activity) (14) and also influences substrate selectivity.…”
Section: Paolo Ascenzimentioning
confidence: 99%